Problem Kesehatan Reproduksi Perempuan Usia Subur Eks Pengungsi Timor Timur - Maria Lupita Nena Meo; Maria Paula Marla Nahak (JURNAL KESEHATAN REPRODUKSI, 2020)
Background: The poverty issue affecting refugees, in principle, aggravates the reproductive health of refugee women..Objective: This study aims to capture the reproductive health problems of the eligible women of the former East Timor refugees in 3 refugee camps in Kupang regencyMethod: This study used a mixed method for 81 eligible women. Data were collected by questionnaire and in-depth interview. Data was analysed univariately and explanatively.Results and Discussion: This study found that 80.2% of women in their early teens at the time of their first pregnancy and 53.1% of eligible women who did not use contraception. Meanwhile, only 43.2% of pregnant women regularly did the Antenatal care (ANC), and only 37% of mothers did exclusive breastfeeding. The qualitative findings found 3 main themes; 1) Teenage pregnancy; 2) Pregnancy control; 3) Barriers in accessing reproductive serviceConclusion: Overall, teenage pregnancy has been a serious problem for refugee women, and it has been aggravated by the low awareness to use contraception and to do ANC. Therefore, the government needs to provide comprehensive, tolerant, and congruent reproductive health services based on culture and complexity of the problems in the refugee camp community. Keywords: Reproductive Health; Women; Refugees; East Timor